Threat factors to the stability of the “faxinal” areas of the Paraná State: the case of the Taquari dos Ribeiros (Terr@ Plural, 2011)
The traditions of the “faxinal” areas, which are based on agriculture, pasture and forestry systems and specific customs, are threatened. Several factors have been deemed responsible, such as the capitalist agribusiness, the presence of “foreigners” in the region, and the influence of new generations. The aim of this research was to investigate the role of these factors on the traditions of the Taquari dos Ribeiros “faxinal”, in the Paraná State, South of Brazil. In order to do so, all families in the community were interviewed. The analysis revealed that these factors had no significant influence in the above-referred issues. However, it was possible to identify a decrease in solidarity in the region. Despite the practice of exchanging implements among tobacco producers, the principles of solidarity are decreasing in most of the Community, regardless of age, which indicates a deep and old problem.